Bronze Age settlement dynamics in a Central European river catchment—The Weiße Elster river (Central Germany) - Miera, Jan Johannes (Frontiers in Environmental Archaeology, 2025)
The paper discusses the potentials and challenges of geoarchaeological research into long-term prehistoric settlement dynamics. As an example, the study employs a dataset of 367 Bronze Age sites from the Weiße Elster river catchment in Central Germany, spanning the area between the Northern German Plain and the Central Uplands. The recorded sites are systematically processed to create a cohesive dataset with a standardized chronology, consistent classification of site types, and clear spatial delineation. A key focus is on analyzing how archaeological, geographical, and culturally intrinsic filters influence the visibility and preservation of Bronze Age sites across time and space. To investigate settlement dynamics, the study uses chronological frequency distributions, site density metrics, spatial relationships between periods, and Site Exploitation Territories (SETs). The results reveal that the basic trends in Bronze Age settlement dynamics can be identified through the dataset. However, there are limitations. Due to culturally intrinsic filters, each period is represented by a distinct combination of settlements, burials, and stray finds. The reason for this is that some periods can only be identified by artifacts made of a certain material, such as pottery or metal. This is also observed in neighboring regions, suggesting broader regional patterns. Site density analyses show that local communities in the Northern German Plain primarily settled along the Weiße Elster River during the Early Bronze Age (2150–1600 BCE) and Middle Bronze Age (1600–1300 BCE). In contrast, sites from the Transitional Period (1300–1150 BCE) show no clear settlement pattern. The Urnfield Period (1150–800 BCE), is marked by a high concentration of sites in the Northern German Plain and increased land use in the Central Uplands. SET analysis aligns with these findings, further highlighting a dominance of loess soils near Early Bronze Age settlements. Site frequencies remain relatively stable between the Early Bronze Age and Transitional Period but surge sharply during the Urnfield Period – a pattern primarily observed in adjacent study areas in the Central Uplands. Notably, both the start of the Middle Bronze Age and the Urnfield Period are characterized by a widespread abandonment of settlements and burial sites from earlier periods.